Pulsed-Ultrasound Irradiation Induces the Production of Itaconate and Attenuates Inflammatory Responses in Macrophages - Yamaguchi A; Maeshige N; Ma X; Uemura M; Noguchi H; Matsuda M; Nishimura Y; Hasunuma T; Kondo H; Fujino H (Dove Medical Press, 2022)
Atomu Yamaguchi,1 Noriaki Maeshige,1 Xiaoqi Ma,1 Mikiko Uemura,1 Hikari Noguchi,1 Mami Matsuda,2 Yuya Nishimura,2 Tomohisa Hasunuma,2,3 Hiroyo Kondo,4 Hidemi Fujino1 1Department of Rehabilitation Science, Kobe University Graduate School of Health Sciences, Kobe, Japan; 2Graduate School of Science, Technology and Innovation, Kobe University, Kobe, Japan; 3Engineering Biology Research Center, Kobe University, Kobe, Japan; 4Department of Food Science and Nutrition, Nagoya Women's University, Nagoya, JapanCorrespondence: Noriaki Maeshige, Department of Rehabilitation Science, Kobe University Graduate School of Health Sciences, 7-10-2 Tomogaoka, Kobe, 654-0142, Hyogo, Japan, Tel +81 78 796 4582, Email nmaeshige@pearl.kobe-u.ac.jpBackground: Itaconate is a key metabolite in the innate immune system and exerts strong anti-inflammatory effects in macrophages. For the production of itaconate in macrophages, immune-responsive gene 1 (IRG1) is an imperative enzyme, and activating the IRG1-itaconate pathway is reported to alleviate inflammatory diseases by upregulating nuclear factor-erythroid 2-related factor 2 (NRF2). However, there are very few reports on strategies to increase itaconate production. Ultrasound therapy is a widely used intervention for anti-inflammatory and soft-tissue regeneration purposes. Here we show the effect of ultrasound irradiation on the production of itaconate in macrophages.Methods: Murine bone marrow-derived macrophages (BMDMs) were exposed to pulsed ultrasound (3.0 W/cm2) for 5 minutes. Three hours after irradiation, the intracellular levels of metabolites and mRNA expression levels of Irg1 and Nrf2 were measured using CE/MS and qPCR, respectively. To evaluate macrophage inflammation status, 3 h after irradiation, the cells were stimulated with 100 ng/mL lipopolysaccharide (LPS) for 1.5 h and the mRNA expression levels of pro-inflammatory factors (Il-1β, Il-6, and Tnf-α) were measured. Student's t-test, one-way ANOVA and Tukey's multiple comparison test were used for statistical processing, and the significance level was set to less than 5%.Results: Ultrasound irradiation significantly increased the intracellular itaconate level and the expression levels of Irg1 and Nrf2 in BMDMs. Upregulation of Il-1β, Il-6, and Tnf-α by LPS was significantly suppressed in BMDMs treated with ultrasound. Ultrasound irradiation did not affect cell viability and apoptosis.Conclusion: Ultrasound irradiation induces the production of itaconate by upregulating Irg1 expression and attenuates inflammatory responses in macrophages via Nrf2. These results suggest that ultrasound is a potentially useful method to increase itaconate production in macrophages.Keywords: itaconate, IRG1, NRF2, pulsed-ultrasound, macrophage, inflammation